Amerykańskie doświadczenia w wydobyciu gazu z łupków - Tarnawski, Marcin (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
With a unique mix of innovation, entrepreneurship and favorable economic conditions, the United States has become the world's largest producer of crude oil and natural gas, and in the near future may become a key exporter of these commodities. Of course, this would not be possible if there were no huge resources in the American territory. However, advanced technology has enabled them to operate. The boom on unconventional raw materials, or rather raw materials extracted by unconventional methods, is so far an American specialty. Although many states have tried, and some continue to do so, no one has succeeded in repeating the success of American entrepreneurs. This work consists of three essential parts. The first concerns issues related to types of unconventional natural gas resources. The second involves the shale revolution in the United States. The third refers to the selected economic aspects of this revolution. The main thesis is that the experiences of the American Revolution are very difficult to replicate in other regions of the world. Due to the specifics of the US mining industry, the deregulated energy market and American legal solutions, it is difficult to expect a repeat of success.
American experience with shale gas
Keywords: shale gas; American energy revolution